If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 2 = 9 + 2x Reorder the terms: 2 + x = 9 + 2x Solving 2 + x = 9 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 2 + x + -2x = 9 + 2x + -2x Combine like terms: x + -2x = -1x 2 + -1x = 9 + 2x + -2x Combine like terms: 2x + -2x = 0 2 + -1x = 9 + 0 2 + -1x = 9 Add '-2' to each side of the equation. 2 + -2 + -1x = 9 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = 9 + -2 -1x = 9 + -2 Combine like terms: 9 + -2 = 7 -1x = 7 Divide each side by '-1'. x = -7 Simplifying x = -7
| 2X+5=55 | | 5X+14=121-10X | | 8-8x=63-43x | | 134=218-g | | 5-7x=-2x+5 | | 3x-1=13x-102 | | 56+56+5x+y=180 | | 3(x-8)+2x=-4 | | -7v+3(v-2)=-18 | | 5x+8=-25+2x | | 66-4x=5x+19 | | 21-3f=9 | | 11-10x=56-31x | | 3X-4=10X-42 | | 5x+208=13x-8 | | 5-10x=45-38x | | 3x-30=15 | | -3x+1=-47+3x | | 3x+72=87 | | (x*x)+160x=6000 | | 7x-2=-2x | | x-9+4x=-54 | | -4x+5y+z=15 | | 3x+31=6x-5 | | 8-10x=24-17x | | 7x+3+6x=-153 | | 15x-2x^2-x^3=0 | | x+3+x=1 | | x^2-15x+6=0 | | 2y^2=5y+3 | | x^2+2-3=0 | | 8x+40=6x-70 |